A conceptual framework and techno-economic analysis of a pelletization-gasification based bioenergy system. (1st September 2019) - Pradhan, Priyabrata; Gadkari, Prabodh; Mahajani, Sanjay M.; Arora, Amit
Graphical abstract: Highlights: A conceptual framework was designed for a bioenergy system for rural India. Agro waste potential was estimated through survey. Techno-economic analysis of an integrated system was conducted. Uncertainty was assessed through Monte-Carlo simulation. Abstract: This paper presents a holistic approach to promote bioenergy in India by designing a conceptual framework that combines resource, technology and market. The proposed concept is an attempt to integrate pelletization and gasification technology for bioenergy system development through an end-to-end approach. The potential of bioenergy resource (i.e. agro waste) was estimated based on survey. The study further assessed the economic feasibility of agro waste pelletization. The economic evaluation was made using indicators such as net present value ( NPV ), internal rate of return ( IRR ), discounted payback period ( DPBP ) etc . Pellet plant capacity of 0.5 ton h −1 showed acceptable economics and the NPV, IRR and DPBP were ₹9.35 million (0.13 million), 41% and 2.8 years, respectively. Moreover, the larger capacity plants (>2 ton h −1 ) were subjected to more risk under low pellet prices (< ₹5 kg −1 or 71.4 ton −1 ). The cash flow statement showed a strong debt paying ability for the project. Pellet price was the most sensitive factor followed by annual operating days on pellet plant economics. Monte Carlo simulation predicted an average NPV of ₹9.3 ± 2.0 million (133.2 ± 29.1 thousand). The economics of fuel pellets utilization in a gasifier for energy applications was also evaluated. The pellet fed gasifier system appeared to be cost competitive with commercial liquefied petroleum gas ( LPG ) and wood at a pellet price range of ₹6.3–8.8 kg −1 (90–126 ton −1 ) in a select scenario. Overall, the designed framework appears to reduce over-dependency on wood or fossil sources, and facilitate bioenergy promotion in rural areas.